Online Business Innovation Strategies In Local Communities In Increasing Economic Competitiveness - Hafel, Rahmadani F; Roroa, Nur Alda Fanny; Djafar, Muhammad Fajrin (Siddiq Institute, 2024)
This research investigates the impact of online business innovations on improving the economic competitiveness of local communities. Using a mixed-method approach, data were collected through surveys, interviews, and observations from 50 participants in rural areas. The findings indicate that adopting e-commerce platforms and enhancing digital skills significantly increased market reach and income. The study highlights the role of collaboration between stakeholders in fostering sustainable economic growth.Â Keyword:Â Online business, local community, business innovation, economic competitiveness, community service